CONTEMPORARY ISLAMIC STUDIES IN INDONESIA: AN INSIGHT AND INTERSECTION - Muh. Rusli (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
This article investigates the development of Islamic Studies in Indonesia over the course of time, focusing on such topics as how the Indonesian government has responded to the subject, the role that education has played, the new problems that the field faces, and how globalization has impacted the field. The following will be discussed as part of the course: the origins and evolution of the academic field of Islamic Studies; the influence that public policy has had on the development of Islamic Studies; the various religious organizations that are responsible for the dissemination of Islamic teachings; research strategies and scholarly networks in Indonesian Islamic Studies; the influence that education has had on Islamic Studies; and the many urgent issues that are currently confronting the academic field. The study finds out that globalization and the media are two factors that have lately contributed to the expansion of Islamic Studies in Indonesia.